TAGS de Joane Hétu et TanGRAM de Danielle Palardy Roger : signatures plurielles et figure continue - Dall’Ara-Majek, Ana (Circuit : musiques contemporaines, 2020)
TAGS by Joane Hétu and TanGRAM by Danielle Palardy Roger are two written works that showcase graphic scores in improvised music. TAGS creates an encounter between Ensemble SuperMusique, the saxophone quartet Quasar, and the Bozzini Quartet. The musicians make “sound graffiti” on an imaginary wall represented by a sequence of timed sections on a descriptive score where the composer uses different instrumental combinations. Using an aesthetic of articulated gestures, the work is made through these multiple signatures. TanGRAM brings together twenty instrumentalists from Ensemble SuperMusique. The game of Tangram is represented in the form of a graphic score where each piece has specific musical properties to be interpreted by the musicians. Rich in combinatorial and symmetrical games, the work presents Orion: a continuous figure, a slowly moving flow where each musician seeks their own way in a global sound.
Keywords: Analyse musicale; Danielle Palardy Roger; Joane Hétu; Musical analysis; graphic score; improvised music; musique improvisée; partition graphique